Chicka Chicka 1-2-3. - Martin, Bill Jr. 1916- (New York, NY : Simon & Schuster, 2004)
Numbers from one to one hundred climb to the top of an apple tree in this rhyming chant.
Keywords: Counting; Stories in rhyme; Sampson, Michael R; Ehlert, Lois, ill